Geosite Bercerita: Strategi Interpretatif Geowisata melalui Papan Informasi di Desa Jari, Bojonegoro - Indriani, Yulia; Aji Prayogo, Dimas Priyo; Fadilah, Rifqo’ Nur; Saputra, Dani Adi; Aini, Anur Rofiqoh (Universitas Pahlawan Tuanku Tambusai, 2025)
Jari Village, located in Gondang District, Bojonegoro Regency, holds significant geotourism potential, particularly through two main geosites: Selo Gajah and Banyu Wedang. However, the lack of interpretative media and limited availability of scientific and cultural information on-site has led to low levels of public and visitor understanding regarding the importance of these geological sites. A community service program conducted by students of the Collaborative Thematic KKN (Community Service Program) from the University of Bojonegoro was carried out to design and install educational information boards that integrate scientific geological narratives with local folklore. Through a participatory approach, the program included the stages of site survey, content development, validation, and installation. The results showed that the information boards had a significant impact on improving public understanding, enriching the tourism experience, and fostering awareness of the need to preserve geological and cultural heritage. This program serves as an integrative model for developing educational and sustainable geotourism.